Kredibilitas Caption Sebagai Syarah Hadits Dalam Media Sosial: Studi Akun Instagram @Fiqihwanita - Anggun Puspita Ningrum; Farhan Suhada; Zaeef Luqmanul Muqtashid (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The purpose of writing this article is to examine the trustworthiness of sources in captions containing hadith sharia. This research uses qualitative methods and library research. The focus of this research is examining the Instagram account @fiqihwanita_ because this media is considered quite popular on this platform. Large uploads need to be limited to sampling. Therefore, the author limits the three hadiths that will be discussed to the theme of the household. Then the analysis technique that the author uses is descriptive analysis, namely analyzing related content and describing the results of the analysis. The results of the research on the three samples found that the Instagram account @fiqihwanita_ did not always include the source of hadith sharia. So in some uploads there is a friendly explanation by the content creator. Then, the sources quoted usually refer to certain websites, such as in this sample there is a reference to muslim.or.id. The writing on the website is summarized and reprocessed so that it is not taken in full due to limited content on the Instagram platform. The caption containing the hadith sharah is also strengthened by taking other hadiths, friends' news, and books such as Fathul Bari to strengthen the explanation.